Assessing Bradykinesia in Parkinsonian Disorders - Pal, Gian; Goetz, Christopher G. (Frontiers in Neurology, 2013)
Objective: Bradykinesia is one of the clinical hallmarks of Parkinson’s disease (PD) and atypical Parkinsonian syndromes. Clinical ratings scales and technology based assessments have been developed to measure bradykinesia. We review the different tools that exist for measurement of bradykinesia and analyze their reliability and applicability to PD and atypical Parkinsonian syndromes. Methods: We summarize data on the factor structure of the two primary scales used to assess PD, the Unified Parkinson’s Disease Rating Scale (UPDRS) and Movement Disorder Society revision of the UPDRS, the MDS-UPDRS. We review how these scales have been used in atypical Parkinsonian syndromes, specifically Progressive Supranuclear Palsy (PSP). Finally, we report on the different technology based tools being used to assess bradykinesia. Results: The UPDRS is a useful measure of PD function and disability with 6 clinically distinct factors, 3 of which pertain to bradykinesia. The MDS-UPDRS has shown high internal consistency and correlation with the original UPDRS. Factor analysis of the UPDRS in PSP reveals 5 clinically distinct factors, 2 of which are independent bradykinesia factors. Thus the UPDRS and MDS-UPDRS are reliable and applicable scales for PD and the UPDRS can be used to assess bradykinesia in PSP. Technology based tools for measuring bradykinesia include gyrosensors, Coordination Ability Test System, Brain Test, quantitative digitography, Motus motion analysis system, PRIMAS, and the At-Home Testing Device. These tools have been compared to the UPDRS motor subscale and are effective in assessing bradykinesia. Conclusion: The UPDRS and MDS-UPDRS are well-established measures of bradykinesia that are applicable and useful in PD. The UPDRS is also been shown to be applicable to PSP. Different technologies exist to measure bradykinesia, though further work is needed to validate these assessment tools and bring them to clinical practice.